2001
DOI: 10.1074/jbc.m009636200
|View full text |Cite
|
Sign up to set email alerts
|

Self-association of the H3 Region of Syntaxin 1A

Abstract: Intracellular membrane fusion requires SNARE proteins found on the vesicle and target membranes. SNAREs associate by formation of a parallel four-helix bundle, and it has been suggested that formation of this complex promotes membrane fusion. The membrane proximal region of the cytoplasmic domain of the SNARE syntaxin 1A, designated H3, contributes one of the four helices to the SNARE complex. In the crystal structure of syntaxin 1A H3, four molecules associate as a homotetramer composed of two pairs of parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…2D). CAPS also failed to interact with the soluble cytoplasmic domain syntaxin-(1-264) likely because it is in a "closed" conformation that occludes interactions with the H3 domain (32). The SPR results confirmed that CAPS interacts with the H3-linker domain of syntaxin-1.…”
Section: Caps-1 Binds Membrane-integrated Syntaxin-1-caps-1mentioning
confidence: 66%
“…2D). CAPS also failed to interact with the soluble cytoplasmic domain syntaxin-(1-264) likely because it is in a "closed" conformation that occludes interactions with the H3 domain (32). The SPR results confirmed that CAPS interacts with the H3-linker domain of syntaxin-1.…”
Section: Caps-1 Binds Membrane-integrated Syntaxin-1-caps-1mentioning
confidence: 66%
“…Like the SNAP-23N homotetramer, the neuronal heterotetramer and complexes between the SNAP-25 coiled-coil domains with the syntaxin-1a coiled-coil domain are arranged as parallel four-helix bundles (7,(23)(24)(25). In contrast, a syntaxin-1a homotetramer contains two pairs of helices that run antiparallel to one another (26). The neuronal heterotetrameric complex has a much larger left-handed helical twist compared with the SNAP-23N homotetramer, because each chain in the heterotetramer has a slightly different conformation.…”
Section: Fig 2 Snare Peptide Binding Assay a Individual Snare Pepmentioning
confidence: 99%
“…Each intermolecular layer of our structure has the same four hydrophobic side chains as a result of the 4-fold symmetry, whereas other SNARE complex structures have different hydrophobic side chains in each layer. The latter is also true for the syntaxin-1a homotetrameric structure, because the chains in this complex are antiparallel (26). Bulky hydrophobic side chains are accommodated by complementary smaller hydrophobic ones in each layer of these other SNARE complex structures (4).…”
Section: Fig 2 Snare Peptide Binding Assay a Individual Snare Pepmentioning
confidence: 99%
“…In addition to the well studied heterotrimeric neuronal and yeast plasma membrane SNARE complexes, other homo-and heteromeric interactions between individual SNAREs have been found and characterized (26)(27)(28). These alternate complexes are less stable than the heterotrimeric SNARE complex, but the relevance of these interactions is unknown.…”
mentioning
confidence: 99%